The strategizing marketing activities in increasing awareness for e-commerce enterprise: a study of Akulaku / Badrulhisham Johar - Johar, Badrulhisham (2017)
The fast and dramatic changes in information technology specially in last one decade has given new concept of marketing in which buyer and seller do not see each other face to face nor see the goods physically; the whole transaction is carried out with the help of 'on line' communication. The entire deal is carried out with the help of computer - telecommunication and net working with associated hardware.